Construction and validation of the chronic acquired polyneuropathy patient‐reported index (CAP‐PRI): A disease‐specific, health‐related quality‐of‐life instrument. Issue 1 (29th December 2015) - Gwathmey, Kelly G.; Conaway, Mark R.; Sadjadi, Reza; Joshi, Amruta; Barnett, Carolina; Bril, Vera; Ng, Eduardo; David, William; Gable, Karissa; Guptill, Jeffrey T.; Hobson‐Webb, Lisa D.; Dineen, Jennifer; et al.
ABSTRACT: Introduction : Generic health‐related quality‐of‐life (HRQOL) patient‐reported outcome measures have been used in patients with chronic immune‐mediated polyneuropathies. We have created a disease‐specific HRQOL instrument. Methods : The chronic acquired polyneuropathy patient‐reported index (CAP‐PRI) was developed and validated in multiple steps. Items were initially generated through patient and specialist input. The performance of the preliminary 20 items was analyzed via a prospective, 5‐center study involving chronic immune‐mediated polyneuropathy patients. Results : Data analysis suggested modification to a 15‐item scale with 3 response categories rather than 5. The final CAP‐PRI was validated in another prospective, 5‐center study. The CAP‐PRI appeared to be a unidimensional outcome measure that fit the Rasch model in our multicenter cohort. It correlated appropriately with outcome measures commonly used in this patient population. Conclusions : The CAP‐PRI is a simple disease‐specific HRQOL measure that appears to be useful for clinical care and possibly also for clinical trials. Muscle Nerve 54 : 9–17, 2016